2021
DOI: 10.1007/s12020-021-02790-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary onion intake and subclinical hypothyroidism in adults: a population-based study from an iodine-replete area

Abstract: Background & AimsThe protective effect of onion against thyroid hypofunction has been reported in animal studies. However, in humans, the association between onion consumption and subclinical hypothyroidism are unclear. The study sought to explore the association between habitual onion intake and subclinical hypothyroidism among adult population from an iodine-replete area. ObjectiveWe aimed to investigate the relationship between dietary onion intake and subclinical hypothyroidism in Chinese population Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Our study suggested high TSH levels (i.e., SCH) played a vital role in triggering metabolic disturbances and clinical symptoms in FEDN MDD patients. In our study, the prevalence of SCH in our sample was 61%, much higher than that in the Chinese general population (range: 3.4%-12.93%) (42)(43)(44). More importantly, we found that TSH levels were highly correlated with the severity of depressive symptoms in FEDN MDD patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Our study suggested high TSH levels (i.e., SCH) played a vital role in triggering metabolic disturbances and clinical symptoms in FEDN MDD patients. In our study, the prevalence of SCH in our sample was 61%, much higher than that in the Chinese general population (range: 3.4%-12.93%) (42)(43)(44). More importantly, we found that TSH levels were highly correlated with the severity of depressive symptoms in FEDN MDD patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Considering the potential effect of iodine on subclinical hyperthyroidism, we conducted this cohort study in Tianjin, an iodine-replete area, and further adjusted for total iodine intake in food in Model 2. Meanwhile, dietary factors are not only associated with H. pylori infection ( 33 ) but also affect the risk of subclinical hyperthyroidism ( 34 ), however, no previous cohort study adjusted for dietary intake when exploring the associations between H. pylori infection and the incidence of subclinical hyperthyroidism, indicating that the risk effect of H. pylori infection on incident subclinical hyperthyroidism might be misestimated. In this large prospective cohort study, we adjusted for dietary factors in the form of three dietary patterns in Model 3, thus, can prevent the influence of dietary factors on the association between H. pylori infection and subclinical hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…, folic acid) 54 and may further affect the observed associations. In Tianjin, people often eat raw, cooked, or a mixture of raw and cooked onions, 55 which is similar in UK. 56–58 However, because data on onion cooking methods were not available in the present study, it is not possible to determine consumption ratios.…”
Section: Discussionmentioning
confidence: 99%